Analisis Kebijakan Regrouping Perguruan Tinggi di Revolusi Industri 5.0 di Indonesia - Desmalia Purba; Masyitha , Masyitha; Haritsah Hammamah Harahap; Irsan Rangkuti; Joharis Lubis (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This study analyzes the policy of regrouping higher education institutions in Indonesia in facing the challenges of the Industrial Revolution 5.0. Through a comprehensive literature study, this study identifies the gap between the current policy of merging higher education institutions and the demands of the Industrial Revolution 5.0 which focuses on human-technology integration. The findings indicate that the regrouping policy requires a more holistic approach and is oriented towards developing institutional capacity to create an adaptive and sustainable higher education ecosystem. This study proposes a regrouping policy framework that considers aspects of digital transformation, strengthening triple helix collaboration, and building institutional capacity based on Society 5.0 values. The implications of the results of this study can be a reference for policy makers in reforming the strategy of merging higher education institutions that are globally competitive but still maintain local wisdom values.